2021
DOI: 10.1097/bpo.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Minimally Invasive Approach for Congenital Vertical Talus With a Comparison Between the Idiopathic and Syndromic Feet

Abstract: Background: Congenital vertical talus (CVT) is a rare congenital foot disorder. Approximately half of the affected children have associated neuromuscular syndromes which may further complicate the treatment. The traditional treatment involved extensive soft tissue and bony reconstructions. The minimally invasive method (Dobbs method/reverse Ponseti) has changed the treatment of CVT. There is significant variation of the reported outcome of this method in the current literature. In this study we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 19 publications
1
27
2
Order By: Relevance
“…34 Hafez and Davis published their series of 21 patients aged 1-17 months with a mean 6.5-year follow-up treated with the minimally invasive method. 35 The five syndromic patients had lower functional scores and 29% recurrence, all occurring in the first postoperative year. None of the idiopathic feet had a recurrence, and no patients required adjunct procedures such as tibialis anterior tendon transfer or anterolateral soft tissue releases.…”
Section: Comparison To Other Methodsmentioning
confidence: 88%
“…34 Hafez and Davis published their series of 21 patients aged 1-17 months with a mean 6.5-year follow-up treated with the minimally invasive method. 35 The five syndromic patients had lower functional scores and 29% recurrence, all occurring in the first postoperative year. None of the idiopathic feet had a recurrence, and no patients required adjunct procedures such as tibialis anterior tendon transfer or anterolateral soft tissue releases.…”
Section: Comparison To Other Methodsmentioning
confidence: 88%
“…Correction can be obtained nearly universally, including patients with teratologic CVT. Nevertheless, recurrence is common in the teratologic feet 47,48. This suggests treatment for CVT should be similar to that of clubfoot and should include preoperative casting followed by a less invasive surgical procedure to obtain reduction of the navicular on the talus.…”
Section: Resultsmentioning
confidence: 99%
“…As the navicular is not yet ossified in younger patients, we used the TAMBA to monitor for both severity and recurrence of talonavicular deformity. In conjunction with past studies, we defined recurrence of talonavicular deformity as a lateral TAMBA measuring >30 degrees in a previously corrected foot and persistent pes valgus as an AP talocalcaneal angle >40 degrees 21,22…”
Section: Methodsmentioning
confidence: 99%
“…Early results from the Dobbs Method have shown lower complication rates with better functional outcomes compared with more extensive surgical treatments 21. Although early results of this technique are encouraging, more research is needed to confirm the previously reported advantages of this new treatment method.…”
mentioning
confidence: 98%